Interpretasi QS. Al-Ahzab: 59 dan Relevansinya terhadap Praktik Hijab Sport Muslimah Gen Z - Muhammad Arif Yasin Bintang; Junaidi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the interpretation of Quranic Surah Al-Ahzab, verse 59, and its relevance to the practice of the sports hijab among Generation Z Muslim women in public sports activities. This verse serves as the primary normative foundation regarding the obligation for Muslim women to cover their aurat; however, its application in the context of modern life—particularly in the world of sports—requires Muslim women to adopt a more contextual and comprehensive understanding. Classical commentaries such as al-Jalalain emphasize the function of the hijab as a marker of social identity and protection for Muslim women,  while contemporary scholar M. Quraish Shihab allows for flexibility in its implementation as long as the fundamental principles of Sharia are upheld. The phenomenon of Gen Z Muslim women actively participating in sports in public spaces while still wearing the hijab indicates the existence of a complex social construction.  Using a library research approach and qualitative-descriptive analysis, this study concludes that the sports hijab is a form of contextualization of Sharia that is valid according to maqashid, not a compromise of religious teachings, as long as it meets the requirements of covering the aurat, is not transparent, and does not outline the body’s contours within an appropriate environmental context.